Relationship between plasma and brain levels and the anticonvulsant effect of lamotrigine in rats - Castel-Branco, Margarida (2003)
The aims of the present research were to characterize the plasma and brain concentration–time profiles of lamotrigine after its acute administration and to establish the relationship between these profiles and the anticonvulsant effect of lamotrigine in rats. Adult male Wistar rats were given 10 mg/kg of lamotrigine intraperitoneally. The lamotrigine profiles in plasma and brain were determined at predetermined times over 120-h post-dose. The anticonvulsant profile against maximal electroshock seizure stimulation was determined over 48 h after dosing. After injection, lamotrigine rapidly appeared in both plasma and brain, suggesting ready penetration of the blood–brain barrier. A linear relationship was established between lamotrigine plasma and brain levels. A linear relationship was also defined between lamotrigine brain levels and the anticonvulsant response. The correspondent plasma levels were also well correlated with the anticonvulsant effect from the moment that the plasma–brain system had reached equilibrium.